PENGARUH MODEL DISCOVERY LEARNING TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR FISIKA SISWA MAN BONDOWOSO - Rizka Hartami Putri; Albertus Djoko Lesmono; Pramudya Dwi Aristya (JURNAL PEMBELAJARAN FISIKA, 2017)
The research focused on the influence of discovery learning. The purposes of this research were to reviewing the effect of discovery learning model to student’s learning motivation in MAN Bondowoso and to knew the effect of discovery learning’s model for student’s physics learning outcomes in MAN Bondowoso. The kind of this research was experiment by posttest only control design. Population of the research was class X at Islamic Senior High School Bondowoso. Technique to collect the data were observation, interview, documentation, test and questionnaire. Technique of data analysis were decriptive and Independent Sample t-test with SPSS 16. The result of independent sample t-test to student’s learning motivation showed value 0,0305≤ 0,05. While the result of independent sample t-test to learning outcomes showed value 0,000 ≤ 0,05. Based on that result could be concluded that: (1) discovery learning model significantly took effect to student’ learning motivation in MA; (2) discovery learning model significantly took effect to student’s physics learning outcomes in MA. Keywords: discovery learning model, learning motivation, student’s learning outcome